2018
DOI: 10.1016/j.ejca.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcomes of patients in the Brain Metastases in Breast Cancer Network Registry

Abstract: Prognosis of patients after developing BMs varies significantly according to the subtype. The outcome in this cohort is similarly poor in triple-negative and HR-positive/HER2-negative patients. Our results underline the high medical need for improvement of treatment and prevention strategies for BMs in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
69
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 22 publications
7
69
0
5
Order By: Relevance
“…The literature review of Lin et al reports a BM rate of 30–55% in patients with metastatic HER2-positive breast cancer and 25–46% in patients with metastatic triple-negative breast cancer [ 9 ]. A median overall survival (OS) of 7.4 months after diagnosis of BM was observed in our previous analysis of the Brain Metastases in Breast Cancer (BMBC) Registry [ 10 ]. The survival rate of patients with BM has not improved over the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review of Lin et al reports a BM rate of 30–55% in patients with metastatic HER2-positive breast cancer and 25–46% in patients with metastatic triple-negative breast cancer [ 9 ]. A median overall survival (OS) of 7.4 months after diagnosis of BM was observed in our previous analysis of the Brain Metastases in Breast Cancer (BMBC) Registry [ 10 ]. The survival rate of patients with BM has not improved over the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, clinical observations have revealed that the prognosis for luminal-like breast cancer differs between patients receiving the same treatment, and the effect of endocrine therapy also differs among patients. 4 Therefore, the current method of categorizing the luminal A and luminal B subtypes according to HER-2 does not meet the need for the refinement of luminal-like breast cancer diagnoses or clinical treatment guidance. It is necessary to further refine the categorization of luminal-like breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Human epidermal growth factor-2 (HER-2)-positive patients have a significantly better prognosis compared with other subtypes, and triplenegative patients have the worst prognosis. 3,4 The various ways of treating of BM include surgery, radiotherapy (whole-brain radiotherapy and stereotactic radiosurgery), and systemic therapy. Corticosteroids and local treatments, including radiotherapy and neurosurgical resection, remain the cornerstones of therapy for BM.…”
Section: Introductionmentioning
confidence: 99%